Corruption and the agricultural production efficiency of the European countries during the recent economic crisis - Hasan, Mohammad Monirul; Tóth, József (Research in Agriculture Livestock and Fisheries, 2015)
This paper examines the association between controls of corruption and the agricultural production efficiency of 23 European Union Member States during the recent economic crisis. Production efficiency, measured in terms of technical efficiency, is the effectiveness of a given set of inputs that is used to produce an output. Owing to climate and geographical location agriculture in European countries is diverse. The economic downturn led by the financial crisis which started in mid-2007, is still prevailing across European countries. Control of corruption along with the existing economic crisis of the member states are affecting agriculture production efficiency. This study used the national level production data for the period of 2003-2009. It shows that the technical efficiency of most Member States have declined over the years and that it was significantly lower in austere economic crisis time 2007-09 than 2003-06 for all countries. It is also found that the declining trend of technical efficiency is significantly lower for central and eastern European countries than for the western European countries. Study finds that the control of corruption in the presence of high government effectiveness, decreases the technical efficiency of agricultural production in the Member States. Res. Agric., Livest. Fish.2(3): 427-437, December 2015